Does Electroacupuncture Have Different Effects on Peripheral and Central Sensitization in Humans: A Randomized Controlled Study - Zheng, Zhen; Bai, Linghan; O’Loughlan, Meredith; Li, Chun Guang; Xue, Charlie C. (Frontiers in Integrative Neuroscience, 2019)
Background: Acupuncture has been shown to be effective in reducing chronic musculoskeletal pain. The common mechanism underlying these pains is peripheral and / or central sensitization. In the clinical setting, it is difficult to separate the peripheral from the central component of pain. Heat/capsaicin-induced hyperalgesia provides a stable, human central sensitization model in which the peripheral component can also be assessed. Aims: This randomized, sham-controlled study aimed to investigate the effect of electroacupuncture (EA) on the severity of heat (peripheral sensitization) and mechanical hyperalgesia (central sensitization) in a pain model in humans. Methods: Twenty-six healthy young participants (24 ± 3.9 years) were recruited. At the baseline, the intensity of sensation to heat stimulation was recorded using modified 10-cm visual analogues scales (VAS). Heat pain thresholds were measured on the forearms. Then heat/capsaicin (45oC for 5 minutes then 0.075% capsaicin for 30 minutes) was applied to the non-dominant forearm to induce hyperalgesia. The primary outcome measures were the size of the area of mechanical hyperalgesia, intensity of pain to heat stimulation and heat pain thresholds. Those were measured at 70 minutes after the initial application of capsaicin. Participants were then randomly allocated to receive either EA (EA, n=14) or sham non-invasive EA (SEA n=12) for 30 minutes. The main outcome measures were assessed again immediately and 90 minutes after EA. Credibility of blinding was assessed. Data were analyzed with t-tests or analysis of variance (ANOVA) where appropriate. Results: Mechanical and heat hyperalgesia were successfully induced. The EA and SEA groups were comparable in their baseline data. Immediately after the allocated acupuncture treatment, the rating to heat stimulation was statistically significantly lower in the EA group than in the SEA group (p < 0.05). The area of mechanical hyperalgesia reduced significantly in both groups without any group difference. No group difference was detected in heat pain threshold. Blinding of the participants was successful. Conclusion: Peripheral and central sensitization in the heat/capsaicin model responded to EA differently, suggesting acupuncture analgesia could vary depending on the types of pain. This observation may explain inconsistent findings from clinical trials of acupuncture.